Effects of household solid fuel use on sarcopenia in middle-aged and older adults: evidence from a nationwide cohort study - Su, Shaohui; Zhou, Yinuo; Wang, Kerui; Liu, Aonan; Lei, Lei; Ma, Hao; Yang, Yanfang (Frontiers in Public Health, 2024)
Background Household solid fuel use is common in global households and has been linked to changes in handgrip strength and muscle mass. However, whether household solid fuel use results in sarcopenia over time is not well elaborated. Methods This study employed data from the 2011–2015 China Health and Retirement Longitudinal Study (CHARLS) that recruited 4,932 participants ≥45 years. The Cox proportional hazards regression model was conducted to estimate the impact of household solid fuel use for cooking and heating on sarcopenia development. The analysis was further stratified based on geographic position. Mediation analysis was employed to estimate the potential mediating effects of cognitive function and depressive symptoms associated with household solid fuel use and sarcopenia. Results Over the 4-year follow-up, 476 cases of sarcopenia were reported (9.65%), with 254 in males (10.82%) and 222 in females (8.59%). Cooking and heating with solid fuels increased the risk of sarcopenia (Cooking: HR 1.401, 95% CI 1.138–1.724; Heating: HR 1.278, 95% CI 1.040–1.571). Crop residue/wood burning correlated with higher sarcopenia risk (Cooking: 1.420, 95% CI 1.147–1.758; Heating: 1.318, 95% CI 1.062–1.635). Switching to clean cooking fuels significantly reduced sarcopenia risk (HR 0.766, 95% CI 0.599–0.979). Heating with solid fuels was associated with higher sarcopenia risk only in southern China (HR 1.375, 95% CI 1.102–1.715). Additionally, cognitive function and depressive symptoms partially mediated the link between household solid fuel use and sarcopenia. Conclusion Household use of solid fuels is associated with an increased risk of sarcopenia. Restricting the use of solid fuels and focusing on cognitive function and depressive symptoms in solid fuel users can help decrease sarcopenia development.